"مخاطــــر التمـــويـل بـعــقــد السَّـلــم فــي المــصارف الإسلاميـــة - بنك البركة الجزائري أنموذجًا - " - أسماء, زاوي (University of Eloued جامعة الوادي, 2019)
عنونت هذه المذكرة: بـــــ"مخاطر التمويل بعقد السلم في المصارف الإسلامية بنك البركة -أنموذجا-"، تحت إشكالية رئيسية: "أين تكمن أهم مخاطر التمويل بعقد السلم المطبق في المصارف الإسلامية؟"، وتمت الإجابة على هذه الإشكالية من خلال ثلاثة مباحث؛ حيث عُني المبحث الأول: بتعريف المخاطر، ومفهوم التمويل الإسلامي، والمبحث الثاني عقد السلم في الفقه الإسلامي ووضحت تعريفه، وشروطه، وأركانه، وحكم عقد السلم في المصارف الإسلامية، أما المبحث الثالث فقد عُني بذكر تقديم عن بنك البركة الجزائري، وتحليل عقد السلم المطبق في المصارف الإسلامية، وختمت هذه الدراسة بعدة نتائج؛ حيث كان من أهمها: إن حسم النزاع، والحفاظ على الحقوق، يكون بتوثيق السلم الموازي بضمانات عدة، ومن هذه الضمانات الكفالة والرهن. The titer of this titled "The risks of financing the peace contract in Islamic banks, Al-Baraka Bank", under the main problem: "Where is the most important financing risks in the peace contract applied in Islamic banks?" The problem was answered through three investigations. The first topic focuses on the Risks definition and the notion of Islamic Financing. The second topic is about Peace Contract in Islamic ‘fiqh’ in which I clarify its definition, its conditions and its basics; and its legality in Islamic banks. The third topic is the mention of the presentation of Al Baraka Bank of Algeria and the analysis of the peace contract applied in Islamic banks. , And concluded this study with several results; where The most important of which: The resolution of the conflict, and the preservation of rights, is to document the parallel peace with several guarantees, including guarantees bail and pledge.
مذكرة ماستر معاملات مالية معاصرة
Keywords: عقد السلم، المخاطر المصرفية، بنك البركة الجزائري.; Peace Contract, Banking Risk, Al Baraka Bank of Algeria.